Development of diagnostic assessment using the I Spring Suite Application in Pancasila Learning in Class V Elementary Schools in Region I, West Padang District - Hafidh, Muhenda; Hendrizal, Hendrizal; Ismira, Ismira (FKIP - Universitas Riau, 2025)
This type of research is development research (R&D) using the 4D model (Define, Design, Develop, Disseminate). The subjects of the study were 3 experts (media experts, material experts, and language experts), 3 teachers, and fifth grade students at SDN 22 Ujung Gurun, SDN 24 Ujung Gurun, and SDN 05 Padang Pasir. The validation results showed a validity level of 93.75% from media experts, 88.63% from material experts, and 90.6% from language experts, all of which were included in the